Experiences of Thrombolytic Therapy for Ischemic Stroke in Tuzla Canton, Bosnia and Herzegovina. (11th March 2014) - Smajlović, Dževdet; Salihović, Denisa; Ibrahimagić, Omer Ć.; Dostović, Zikrija; Avdić, Leila; Vidović, Mirjana
Abstract : Aim . To demonstrate our experiences of thrombolytic therapy in acute ischemic stroke. Subjects and Methods . Patients with ischemic stroke treated with rt-PA, admitted at the Department of Neurology, Tuzla, Bosnia and Herzegovina, in the period between April 1, 2008, and December 31, 2012, were included. Results . Between April 2008 and December 2012, intravenous rt-PA was given to 87 patients with acute ischemic stroke, which represents 3.2% of patients with acute ischemic stroke admitted to our department in that period. Hypertension was the leading stroke risk factor. The mean NIHSS score before thrombolysis was 12 (range 4–21). Large artery arteriosclerosis was the most common stroke etiology. The mean door-to-needle time was 72 minutes and onset-to-needle time 152 minutes. Half of patients (44/87) had a significant improvement within the first 24 hours. Parenchymal hemorrhage occurred in 5 patients (6%) and was fatal in two cases. At 3-month follow-up, 45% of patients (39/87) had good outcome (mRS 0 or 1). Sixteen patients were dead at 3 months, and mean baseline stroke severity was significantly higher in patients who died (NIHSS 16.5 versus 11, P = 0.003 ). Conclusion . The number of patients with acute ischemic stroke treated using rt-PA in the Department of Neurology, Tuzla, is lower than in developed countries. Thrombolytic therapy is safe and leads to favorable outcome in half of the patients.